Antrodia cinnamomea May Interfere with the Interaction Between ACE2 and SARS-CoV-2 Spike Protein in vitro and Reduces Lung Inflammation in a Hamster Model of COVID-19 - Li LH; Chiu HW; Wong WT; Huang KC; Lin TW; Chen ST; Hua KF (Dove Medical Press, 2023)
Lan-Hui Li,1 Hsiao-Wen Chiu,2 Wei-Ting Wong,2 Ko-Chieh Huang,3 Tzu-Wen Lin,3 Shui-Tein Chen,3 Kuo-Feng Hua2,4 1Department of Laboratory Medicine, Linsen, Chinese Medicine and Kunming Branch, Taipei City Hospital, Taipei, Taiwan; 2Department of Biotechnology and Animal Science, National Ilan University, Yilan, Taiwan; 3ALPS Biotech Co. Ltd, Taipei, Taiwan; 4Department of Medical Research, China Medical University Hospital, China Medical University, Taichung, TaiwanCorrespondence: Kuo-Feng Hua, Department of Biotechnology and Animal Science, National Ilan University, No. 1, Sec. 1, Shennong Road, Yilan, 260, Taiwan, Tel +886 3 931 7626, Fax +886 3 935 4794, Email kuofenghua@gmail.comPurpose: Coronavirus disease 2019 (COVID-19) poses a global health challenge with widespread transmission. Growing concerns about vaccine side effects, diminishing efficacy, and religious-based hesitancy highlight the need for alternative pharmacological approaches. Our study investigates the impact of the ethanol extract of Antrodia cinnamomea (AC), a native medicinal fungus from Taiwan, on COVID-19 in both in vitro and in vivo contexts.Methods: We measured the mRNA and protein levels of angiotensin-converting enzyme-2 (ACE2) in human lung cells using real-time reverse transcriptase-polymerase chain reaction and Western blotting, respectively. Additionally, we determined the enzymatic activity of ACE2 using the fluorogenic peptide substrate Mca-YVADAPK(Dnp)-OH. To assess the impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, we used SARS-CoV-2 pseudovirus infections in human embryonic kidney 293T cells expressing ACE2 to measure infection rates. Furthermore, we evaluated the in vivo efficacy of AC in mitigating COVID-19 by conducting experiments on hamsters infected with the Delta variant of SARS-CoV-2.Results: AC effectively decreased ACE2 mRNA and protein levels, a critical host receptor for the SARS-CoV-2 spike protein, in human lung cells. It also prevented the spike protein from binding to human lung cells. Dehydrosulphurenic acid, an isolate from AC, directly inhibited ACE2 protease activity with an inhibitory constant of 1.53 μM. In vitro experiments showed that both AC and dehydrosulphurenic acid significantly reduced the infection rate of SARS-CoV-2 pseudovirus. In hamsters infected with the Delta variant of SARS-CoV-2, oral administration of AC reduced body weight loss and improved lung injury. Notably, AC also inhibited IL-1β expression in both macrophages and the lung tissues of SARS-CoV-2-infected hamsters.Conclusion: AC shows potential as a nutraceutical for reducing the risk of SARS-CoV-2 infection by disrupting the interaction between ACE2 and the SARS-CoV-2 spike protein, and for preventing COVID-19-associated lung inflammation.Graphical Abstract: Keywords: coronavirus disease 2019, angiotensin-converting enzyme-2, severe acute respiratory syndrome coronavirus 2, Antrodia cinnamomea, the intracellular sensor NACHT, LRR, PYD domain-containing protein 3 inflammasome, cytokine